1996
DOI: 10.1002/(sici)1098-2280(1996)27:2<110::aid-em6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the ciprofloxacin-induced mutations in Salmonella typhimurium

Abstract: The mutagenic events induced by ciprofloxacin, a potent antimicrobial agent, have been characterized. For this, a battery of His− mutants of Salmonella typhimurium (hisG428, hisG46, hisC9070, and hisG1775 targets) that detects the six possible transitions and transversions [Levin and Ames (1986): Environ Mutagen 8:9–28] and two additional His− strains (hisC3076 and hisD3052 targets) carrying frameshift mutations have been used. Our results indicate that GC→TA transversions are the major base‐pair substitution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
7

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
2
0
7
Order By: Relevance
“…Fluoroquinolone-resistant mutants will be selected only if the concentration of the antibiotic is less than 8-fold the MIC [2], and underdosing appears to predispose for the selection of resistant strains [6,22]. Giraud et al [10] confirmed this in a study where they found that one single administration of a low dose of enrofloxacin was sufficient to select resistant isolates under in vivo experimental conditions in monocontaminated gnotoxenic chickens.…”
Section: Association Between Fluoroquinolone Consumption and Resistancementioning
confidence: 99%
“…Fluoroquinolone-resistant mutants will be selected only if the concentration of the antibiotic is less than 8-fold the MIC [2], and underdosing appears to predispose for the selection of resistant strains [6,22]. Giraud et al [10] confirmed this in a study where they found that one single administration of a low dose of enrofloxacin was sufficient to select resistant isolates under in vivo experimental conditions in monocontaminated gnotoxenic chickens.…”
Section: Association Between Fluoroquinolone Consumption and Resistancementioning
confidence: 99%
“…Los antecedentes sostienen que la actividad de la proteína UvrB es necesaria para la mutagénesis mediada por ciprofloxacina (3,13). No obstante, los estudios de cepas con la delección uvrB han cuestionado dicho requerimiento (7,22).…”
Section: Requerimiento De La Actividad Uvrbunclassified
“…No resulta contradictorio cuando se afirma que las quinolonas tienen la particularidad de presentar una escasa o nula actividad mutagénica, tanto en E. coli como en S. enterica Typhimurium; por lo que en los diversos ensayos bacterianos para detectar su mutagénesis, es imprescindible que las cepas cuenten con ciertos requerimientos genéticos mínimos; caso contrario, la carencia de expresión de determinados genes no promovería completamente la aparición de mutagenésis (13,27,28,29,30).…”
Section: 3-requerimiento De La Actividad Uvraunclassified
See 2 more Smart Citations